A RESEARCH VIEW OF THE INTEGRATION OF GRAPHING CALCULATORS INTO THE SCHOOL MATHEMATICS CLASSROOM - Allan Leslie White (Study Program of Mathematics Education of Unimed Postgraduate Program, 2008)
Teachers play a key role in the integration of the graphing calculator into the teaching and learning of classroom mathematics. Research points to the influence that knowledge and beliefs of teachers play in the quality of classroom use of graphing calculator. It has been argued that there are five broad categories of teacher response when it comes to the integration of technology within their classroom. Teachers tend to view technology as either: a demon; a servant; an idol; a partner; or, a liberator. These categories are used to discuss a selection of research findings and their implications for graphing calculators while providing possible directions for future researchers investigating the integration of graphing calculators into the teaching and learning of classroom mathematics.